Pediatric Interstitial Lung Disease Masquerading as Difficult Asthma: Management Dilemmas for Rare Lung Disease in Children - EY Chan; Sharon D Dell (Canadian Respiratory Journal)
Idiopathic nontransplant-related childhood bronchiolitis obliterans is an uncommon disease. Most patients present with chronic recurrent dyspnea, cough and wheezing, which are also features of asthma, by far a much more common condition. The present case study reports on a six-year-old girl who presented to a tertiary care centre with recurrent episodes of respiratory distress on a background of baseline tachypnea, chronic hypoxemia and exertional dyspnea. Her past medical history revealed significant lung disease in infancy, including respiratory syncytial virus bronchiolitis and repaired gastroesophageal reflux. She was treated for 'asthma exacerbations' throughout her early childhood years. Bronchiolitis obliterans was subsequently diagnosed with an open lung biopsy. She did not have sustained improvement with systemic corticosteroids, hydroxychloroquine or clarithromycin. Cardiac catheterization confirmed the presence of secondary pulmonary hypertension. Treatment options remain a dilemma for this patient because there is no known effective treatment for this condition, and the natural history is not well understood. The present case demonstrates the need for careful workup in 'atypical asthma', and the urgent need for further research into the rare lung diseases of childhood.